Correlation Between Maternal Smoking During Pregnancy and Dental Caries in Children: A Systematic Review and Meta-Analysis - Zhong, Yongjin; Tang, Quan; Tan, Bowen; Huang, Ruijie (Frontiers in Oral Health, 2021)
Background: Dental caries is a long-standing oral health problem for children all over the world. The available evidence shows that the association between maternal smoking during pregnancy and childhood caries is still controversial. Therefore, the aim of this systematic review and meta-analysis was to determine whether there was a correlation of prenatal smoking and dental caries in children. Methods: PubMed, EMBASE, Cochrane, Web of Science, and Scopus databases were searched for observational studies assessing the relationship between maternal smoking during the pregnancy and childhood caries. According to the predesigned eligibility criteria and items, studies selection, and data extraction were conducted, respectively. The effect estimates were pooled using a fixed-effect model or a random-effect model. Newcastle-Ottawa Scale (NOS) was adopted to evaluate the methodological quality of the included studies. All analyses were carried out through Stata 12.0 software. Results: Our systematic review included a total of 11 studies, of which 6 cross-sectional studies and 3 longitudinal studies were included in the final meta-analysis. The pooled estimates indicated maternal smoking during pregnancy was significantly associated with dental caries in children both in cross-sectional studies (OR = 1.57, 95% CI = 1.47–1.67) and longitudinal studies (RR = 1.26, 95% CI = 1.07–1.48). Sensitivity analyses confirmed the overall effect estimates were robust. Conclusions: There is a significant correlation of maternal smoking during pregnancy and childhood caries. However, the causal relationship between them cannot be determined. More prospective and extensive studies on this theme is needed for verification. Even so, it is necessary for pregnant women and women of reproductive age to quit smoking. Strategies must be developed to raise public awareness about the impact of prenatal smoking on children's oral health.